1998
DOI: 10.1152/ajplung.1998.275.1.l96
|View full text |Cite
|
Sign up to set email alerts
|

Induction of arginase isoforms in the lung during hyperoxia

Abstract: l-Arginine can be metabolized by nitric oxide (NO) synthase (NOS) to produce NO or by arginase to produce urea andl-ornithine. In the liver, arginase (the AI isoform) is a key enzyme in the urea cycle. In extrahepatic organs including the lung, the function of arginase (the AII isoform) is less clear. Because we found that lung AII was upregulated during 100% O2exposure in preliminary experiments, we sought to characterize expression of the arginase isoforms and inducible NOS and to assess the functions of arg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
0
8

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(107 citation statements)
references
References 19 publications
3
96
0
8
Order By: Relevance
“…In the newborn rat, we (5) have previously reported that chronic hyperoxia induces pulmonary hypertension. Hyperoxia is known to upregulate arginase expression in lung (29) and possibly contributed to decreased NO production that we reported in this newborn model of pulmonary hypertension (5).…”
Section: Discussionsupporting
confidence: 53%
“…In the newborn rat, we (5) have previously reported that chronic hyperoxia induces pulmonary hypertension. Hyperoxia is known to upregulate arginase expression in lung (29) and possibly contributed to decreased NO production that we reported in this newborn model of pulmonary hypertension (5).…”
Section: Discussionsupporting
confidence: 53%
“…Arginase II also plays a role in collagen synthesis as was shown in a murine model of bleomycin-induced fibrosis. 33 In addition, Que and colleagues 34 showed the induction of arginase I and II during the fibroproliferative phase of hyperoxic lung injury in rats. The increase in arginase II in our model when peribronchiolar fibrosis (40 days) is observed is consistent with its involvement in repair processes.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperoxic-mice of each strain were exposed continuously to >99% O 2 (flow rate of 10 L/min; CO 2 <0.1%; temp=25-26°C; and humidity<40%) in polystyrene chambers for 72 hours as described previously (Que et al 1998;Folz et al 1999), except for 10 min/day when the cages were opened to room air for general maintenance. The air-exposed control mice from each strain were housed in the same chambers and exposed to room air under identical flow, temperature, and humidity conditions for the same time period.…”
Section: Exposuresmentioning
confidence: 99%